Розширення функціональних можливостей табличних цифрових синтезаторів ЛЧМ сигналів - Хохлов, Д. В.; Никитюк, О. О. (ХНУРЕ, 2024)
A feature of the considered synthesizers is the use of a multi-stage procedure for generating a chirp signal from several fragments. At the same time, at each stage of operation, acceptable conditions are provided for frequency selection of the required component of the spectrum of a discrete signal, and the frequency, phase and time parameters of which are strictly coordinated with each other. The resulting signal is ultra-wideband, and its frequency bandwidth is commensurate with the clock speed.
Keywords: синтезатор ЛЧМ сигналів; цифровий синтезатор